HUBUNGAN PENGGUNAAN MULTIMEDIA TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS VA SD NEGERI 37 PEKANBARU - Nur, Zullayli; Ain, Siti Quratul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
In the context of elementary school education, students' interest in science subjects is often less than optimal due to the perception of difficulty and the abstract nature of the material. This study aims to determine the relationship between the use of multimedia and students' interest in science education at the elementary school level. This study uses a quantitative approach method. The quantitative approach is also called a positivist approach because it is based on the philosophy of positivism. Research is conducted to compare the similarities and differences between two or more facts based on a certain framework of thought. to find out how one treatment with controlled conditions correlates with another. The data technique used in this study is the